Utilization of Novel (KNbO3)1-x(Ba2FeNbO6)x (x=0.1, 0.2, 0.3) Solid Solutions for Efficient Photo-Assisted Fenton Degradation of Methylene Blue Dye - Avcioglu, Celal; Kraus, Peter; Avcioglu, Suna; Mueller, Julian T.; Gurlo, Aleksander; Bekheet, Maged F. (WILEY, 2025)
Novel (KNbO3)1-x(Ba2FeNbO6)x (x = 0.1, 0.2, 0.3) solid solutions corresponding to K0.82Ba0.18Fe0.09Nb0.91O3, K0.64Ba0.36Fe0.18Nb0.82O3, and K0.46Ba0.54Fe0.27Nb0.73O3 compounds have been synthesized via molten salt method. X-ray diffraction confirms the formation of solid solutions, while transmission electron microscopy combined with energy-dispersive spectroscopy results demonstrates a homogeneous distribution of elements. The obtained solid solutions crystallized in a cubic crystal structure, whereas the parent KNbO3 possesses an orthorhombic structure. The wide bandgap semiconductor KNbO3 transformed into a visible-light-active material, with its bandgap energy reduced from 3.56 eV to approximate to 2.4 eV. The substitution of K in KNbO3 with Ba is responsible for structural modification from orthorhombic to cubic symmetry, whereas both structural modification and the substitution of Nb with Fe correlated with optical properties. The photocatalytic activities of all obtained solid solutions are improved compared with the parent KNbO3 and Ba2FeNbO6 compounds for photocatalytic degradation of methylene blue (MB) dye. Among the series of solid solutions, K0.82Ba0.18Fe0.09Nb0.91O3 photocatalysts show the highest MB removal efficiency owing to its relatively higher surface area, suppressed charge carrier recombination, and more negative conduction band edge. Moreover, K0.82Ba0.18Fe0.09Nb0.91O3 photocatalyst (0.1 g) combined with hydrogen peroxide (H2O2) to form a novel photo-Fenton system, achieving almost complete degradation of 100 mL of 10 mg L-1 MB dye in 30 min.
Keywords: photocatalytic dye degradation; perovskite solid solutions; photocatalysis; photo-Fenton process; potassium niobate; PHOTOCATALYSTS; LUMINESCENCE; Science & Technology - Other Topics; Energy & Fuels; Materials Science